Analysis of Elymus nutans seed coat development elucidates the genetic basis of metabolome and transcriptome underlying seed coat permeability characteristics - Zhou, Jing; Li, Yan; Wang, Xun; Liu, Yijia; David-Schwartz, Rakefet; Weissberg, Mira; Qiu, Shuiling; Guo, Zhenfei; Yang, Fulin (Frontiers in Plant Science, 2022)
The seed coat takes an important function in the life cycle of plants, especially seed growth and development. It promotes the accumulation of nutrients inside the seed and protects the seed embryo from mechanical damage. Seed coat permeability is an important characteristic of seeds, which not only affects seed germination, but also hinders the detection of seed vigor by electrical conductivity method. This research aimed to elucidate the mechanism of seed coat permeability formation through metabolome and transcriptome analysis of Elymus nutans. We collected the samples at 8, 18, and 28 days post-anthesis (dpa), and conducted a seed inclusion exosmosis experiment and observed the seed coat permeability. Moreover, we analyzed the changes in the metabolome and transcriptome during different development stages. Here, taking 8 dpa as control, 252 upregulated and 157 downregulated differentially expressed metabolites were observed and 886 upregulated unigenes and 1170 downregulated unigenes were identified at 18 dpa, while 4907 upregulated unigenes and 8561 downregulated unigenes were identified at 28 dpa. Meanwhile, we observed the components of ABC transporters, the biosynthesis of unsaturated fatty acids, and phenylalanine metabolism pathways. The key metabolites and genes affecting seed coat permeability were thiamine and salicylic acid. Furthermore, there were 13 and 14 genes with correlation coefficients greater than 0.8 with two key metabolites, respectively, and the ǀlog2Fold Changeǀ of these genes were greater than 1 at different development stages. Meanwhile, pathogenesis-related protein 1 and phenylalanine ammonia-lyase play an important role in regulating the formation of compounds. Our results outline a framework for understanding the development changes during seed growth of E. nutans and provide insights into the traits of seed coat permeability and supply a great significance value to seed production and quality evaluation.